Animal Models of Eating Disorders - Avena, Nicole M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
The growth of the field of eating disorder research has led to a vast array of empirical articles, and the development of new animal models that can be used to study these disorders continues to stimulate new research.  Animal Models of Eating Disorders serves as a collection of detailed techniques contributed by experts in the field who are well-versed in the development and implementation of these models. Since eating disorders are complex and likely due to a combination of environmental, genetic, and social causes, the detailed chapters of this volume have been designed to highlight different contributing factors. Collectively, these chapters give a comprehensive and representative overview of both recently developed and classic methodologies used in the study of eating disorders.  Written for the popular Neuromethods series, this work contains the kind of thorough description and implementation advice that promises successful results.   Authoritative and practical, Animal Models of Eating Disorders aims to aid researchers in the use of animal models to assist in their investigation and characterization of the behaviors and neurochemical alterations associated with these devastating disorders.
Introduction: Binge Eating, Bulimia Nervosa, and Hedonic Overeating -- Binge-Prone vs. Binge-Resistant Rats and Their Concomitant Behavioral Profiles -- Binge Eating in Female Rats Induced by Yo-Yo Dieting and Stress -- Binge-Type Eating Induced by Limited Access to Optional Foods -- Assessment of Stress-Independent Binge-Like Eating Behavior in Mice -- Predicting and Classifying Rats Prone to Overeating Fat -- Modeling Binge Eating in Non-Human Primates -- Psychosocial Stress and Diet History Promote Emotional Feeding in Female Rhesus Monkeys -- Stressful Experiences in Early Life and Subsequent Food Intake -- Sham Feeding in Rats Translates Into Modified Sham Feeding in Women with Bulimia Nervosa and Purging -- Animal Models of Binge Eating Palatable Foods: Emergence of Addiction-Like Behaviors and Brain Changes in the Rat -- Deep Brain Stimulation for the Treatment of Binge Eating: Mechanisms and Preclinical Models -- Saccharin Preference in Rats: Relation to Impulsivity and Drug Abuse -- Food Seeking in Spite of Harmful Consequences -- Introduction: Anorexia and Undereating -- Food Restriction and Reward in Rats -- Activity-Based Anorexia in the Rat -- Food-Anticipatory Activity: Rat Models and Underlying Mechanisms -- Anorexia and Drugs of Abuse Abnormally Suppress Appetite, the Result of a Shared Molecular Signal Foul-Up -- The Anorectic Phenotype of the Anx/anx Mouse is Related to Hypothalamic Dysfunction -- Functional Magnetic Resonance Imaging in Awake Rats: Studies Relevant to Addiction and the Reward Circuitry.
Keywords: Neurosciences; Psychiatry; Animal models in research; Neurosciences; Psychiatry; Animal Models